RENDIMENTO DE CARCAÇA E CORTES DE FRANGOS DE CORTE CRIADOS EM DIFERENTES DENSIDADES DE CRIAÇÃO - MELLO, Bruna Finotti Fonseca Reis; OLIVEIRA, Andréia Fróes Galuci; HENRIQUE, Cleoneide dos santos; SILVA, Eduardo Santos; SOUZA, Jéssica Andrade Diniz; BUZATTO, Lara Oliveira (ANAIS DO ENIC, 2017)
-